Amplificação cruzada de locos de microssatélites em Crustacea Decapoda - Silva, Tális de Oliveira (2008)
Aeglidae Dana (1852) are anomuran crabs which occur exclusively in freshwater. The genus Aegla consists of 63 species and subspecies restricted to the southern South America. Highly sensitive molecular markers can help to elucidate some evolutionary features of the genus. Microsatellite markers are excellent molecular markers because they can reveal fine details of the genetic structure of a population. However, microsatellite isolation employs a laborious and expensive methodology. An alternative approach to the isolation procedure is the utilization of microsatellite markers previously developed for close species. The closer the phylogenetic relationship between two species, the more probable is the conservation of the loci and the successful cross-amplification. The present study aimed to test the crossamplification of microsatellite loci developed for two species of the family Aeglidae in other decapod crustaceans and to verify their potential for application in further studies on population genetics. Primers developed for microsatellite loci previously isolated from Aegla longirostri (AlCA135 and AlCA138) and Aegla uruguayana (Au05) were tested in seven species of the family Aeglidae, Aegla camargoi, Aegla leptodactyla, Aegla plana, Aegla platensis, Aegla spinipalma, Aegla violacea and Aegla sp.n., besides in Emerita brasiliensis (Anomura: Hippidae), Pachycheles laevidactylus (Anomura: Porcellanidae) and Trichodactylus panoplus (Brachyura: Trichodactylidae). DNA was extracted using traditional procedures. DNA samples were submitted to the Polymerase Chain Reaction (PCR) using the primers cited. The PCR products were electrophoresed in 6% polyacrylamide gels, at 100V for 24 hours. The gels were silver-stained and the band patterns were analyzed. The microsatellite markers could be transferred only within the genus Aegla, and the locus AlCA135 presented the greatest rate of success in cross-species transfer. Cross-amplification between families within the infra-order Anomura, as well as between the infra-order Anomura and Brachyura was not possible, indicating that these microsatellite loci are not conserved in distantly related species. Notwithstanding, the evaluated loci present potential for utilization within the family Aeglidae and new tests, using optimized PCR conditions, should improve the success rate in cross-amplification.